Dźwięk i znaczenie w Truposzu Jima Jarmuscha - Bitka, Stanisław (Przestrzenie Teorii, 2019)
The aim of the article is to prove that the Dead Man soundtrack written by Neil Young plays an essential part in understanding and interpreting Jim Jarmusch’s film. The author of the article highlights the meaningful role of Dead Man in the director’s oeuvre, analyses the film’s structure, examines the process of recording the soundtrack as well as characterizes the selected scenes. He singles out the music motifs, their functions, and outlines the musical and dramatic effect of the film.